Evaluation of MWCNT as fuel additive to diesel–biodiesel blend in a direct injection diesel engine. Issue 2 (7th February 2023) - Solmaz, Hamit; Calam, Alper; Yılmaz, Emre; Şahin, Fatih; Ardebili, Seyed Mohammad Safieddin; Aksoy, Fatih
Abstract: In this study, effects of multi-walled carbon nanotube (MWCNT) addition to waste frying oil biodiesel (B20) on performance, combustion, and exhaust emissions in a direct-injection compression ignition engine were investigated. Experiments were carried out at maximum engine torque speed and four different engine loads. The results show that engine performance has deteriorated somewhat by using B20 fuel without MWCNT additive compared with neat diesel. The addition of MWCNT to B20 improved fuel properties. This occurred because MWCNT additive improved engine performance. By using 100 ppm additive to B20 fuel, the combustion duration has been shortened compared to neat diesel, indicating that thermal efficiency has increased with the decrease of heat losses. The highest indicated thermal efficiency was recorded as 33.16% at 15 Nm engine load using 100 ppm additive to B20 test fuel. Also, 100 ppm additive to B20 test fuel reduced hydrocarbon, CO and soot emissions by 41, 36.4 and 31.8%, respectively, compared to reference neat diesel fuel. The MWCNT additive improved the in-cylinder combustion reactions, thereby increasing engine performance. With the improvement of combustion, in-cylinder gas temperatures increased. For this reason, higher NOx emissions were obtained using MWCNT additive fuels compared to neat diesel.